Detection of virulence-related genes in Lactococcus garvieae and their expression in response to different conditions - Eraclio, Giovanni; Ricci, Giovanni; Quattrini, Mattia; Moroni, Paolo; Fortina, Maria Grazia (Folia microbiologica, 2018)
Lactococcus garvieae has emerged as an important zoonotic pathogen. However, information regarding mechanisms and factors related to its pathogenicity is lacking. In the present study, we investigated the distribution and functionality of genes related to virulence factors in L. garvieae strains isolated from different niches (diseased fish, humans, meat and dairy products, vegetables), using both post-genomic and genotypic analysis. Putative genes encoding hemolysin, fibronectin-binding protein, and penicillin acylase were detected in all analyzed genomes/strains. Their expression was significantly induced by bile salt stress. Putative genes encoding bile salt hydrolase were found in a few strains from dairy and human sources, as well as the mobilizable tet genes. Finally, all genomes possessed a folate gene cluster, in which mutations in the dihydropteroate synthase gene (folP) could be related to sulfonamide resistance. To the best of our knowledge, this is the first study aimed to explore the pathogenic potential of L. garvieae through the analysis of numerous L. garvieae genomes/strains, coming from different sources. This approach allowed the detection of virulence-related genes not yet investigated in the species and the study of their expression after exposure to different environmental stresses. The results obtained suggest a virulence potential in some L. garvieae strains that can be exploited for survival in the human gastrointestinal tract.
Keywords: regulace genové exprese u bakterií; faktory virulence; Gene Expression Regulation, Bacterial; genomika; DNA bakterií; Animals; DNA, Bacterial; Gene Expression Profiling; Humans; Genomics; lidé; zvířata; Lactococcus; Virulence Factors; stanovení celkové genové exprese